Emerging Infectious Diseases in Water Buffalo An Economic and Public Health Concern - Villanueva, Marvin A.; Mingala, Claro N.; Alexis Tubalinal, Gabriel S.; Blanca Gaban, Paula V.; Nakajima, Chie; Suzuki, Yasuhiko (IntechOpen, 2018)
Water buffalo is of great significance for the livestock industry worldwide because of its food value and agricultural importance. Thanks to its adaptability to tropical climate, innovative breeding and animal husbandry, its role in the industry has increased over time. However, vast economic losses have also been experienced in this sector due to infectious diseases that primarily affect the reproduction of water buffaloes. This book provides current information on emerging infectious diseases in water buffalo - bacterial (leptospirosis, brucellosis, and bovine tuberculosis), viral (bovine ephemeral fever, rotaviral infection, and bovine viral diarrhea), protozoal (trypanosomiasis, neosporosis, and cryptosporidiosis), fungal (Deg Nala disease), and endoparasitic pathogen infections (fasciolosis and schistosomiasis) - including their manifestations, mode of transfer, diagnostic protocols, eradication process, and control measures applied. Therefore, this book should contribute to a better understanding of the mechanisms of these diseases, as well as how to control and manage these kinds of infections. Furthermore, the book contains data regarding the huge impact of these infections and how vastly they have affected the sector's economic performance.